FACTORS RELATED TO INSURANCE PURCHASE INTENTION IN THAILAND - Krajaechun, Santi; Praditbatuga, Piyathida (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
The objective of this study was to determine the factors that influence consumer purchase intention towards (non-life) insurance in Thailand, based on the Theory of Reasoned Action model (Fishbein & Ajzen, 1980). Data were collected via questionnaires applying convenience sampling method. Five hundred sets of questionnaires were distributed to Thai citizens in Bangkok and nearby who would like to purchase non-life insurance policy once the reliability and validity of the instrument were established. A total of 385 questionnaires were completed and returned. The independent variables were the attitude towards the product (insurance service provider’s competence, consumers’ monetary attitude towards insurance, the positivity of consumers’ insurance experience, the possibility to reduce the number of premiums payable for insurance, and the acceptability of insurance conditions) and subjective norms. The dependent variable was an insurance purchase intention. Frequency and percentage were used to analyze the demographic profile. Mean and the standard deviation was used to analyze respondents’ perception of the main variables. Hypotheses were tested with Pearson’s correlation coefficient. The results from Pearson’s correlation coefficient demonstrated that attitude towards the product in terms of acceptability of non-life insurance conditions and subjective norms significantly related to intention to purchase non-life insurance. However, attitude towards the product in terms of acceptability of non-life insurance conditions (r = 0.233) had a stranger relationship with insurance purchase intention than subjective norms (r = 0.103).